2006
DOI: 10.1074/jbc.m601231200
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Rearrangements of the Kv2.1 Potassium Channel Termini Associated with Voltage Gating

Abstract: The voltage-gated K v 2.1 channel is composed of four identical subunits folded around the central pore and does not inactivate appreciably during short depolarizing pulses. To study voltageinduced relative molecular rearrangements of the channel, K v 2.1 subunits were genetically fused with enhanced cyan fluorescent protein and/or enhanced yellow fluorescent protein, expressed in COS1 cells, and investigated using fluorescence resonance energy transfer (FRET) microscopy combined with patch clamp. Fusion of fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 28 publications
3
26
0
Order By: Relevance
“…The interaction between N and C termini of several Kv channels, including Shaker, Kv1.2 and Kv2.1, has been suggested before (Schulteis et al, 1996;Ju et al, 2003;Scholle et al, 2004;Long et al, 2005;Kobrinsky et al, 2006). In this study, we have provided evidence that the N/C terminal interaction of Kv3.1 channels is mediated by a direct, Zn 2ϩ -dependent binding between the T1 domain and the ATM region (Figs.…”
Section: Direct Interaction Between the T1 Domain And The Atm Regionsupporting
confidence: 64%
“…The interaction between N and C termini of several Kv channels, including Shaker, Kv1.2 and Kv2.1, has been suggested before (Schulteis et al, 1996;Ju et al, 2003;Scholle et al, 2004;Long et al, 2005;Kobrinsky et al, 2006). In this study, we have provided evidence that the N/C terminal interaction of Kv3.1 channels is mediated by a direct, Zn 2ϩ -dependent binding between the T1 domain and the ATM region (Figs.…”
Section: Direct Interaction Between the T1 Domain And The Atm Regionsupporting
confidence: 64%
“…Bearing in mind that Syx binds at the CTs (Regev et al, 2009), this suggested a possible cross talk between closely positioned N and C termini. Notably, N-C close associations that are involved in the gating and activation of many channel types have been demonstrated (Varnum and Zagotta, 1997;Schulte et al, 1998;Tucker and Ashcroft, 1999;Qu et al, 2000;Lippiat et al, 2002;Tsuboi et al, 2004;Kobrinsky et al, 2006). Furthermore, using FRET analysis, our laboratory has recently demonstrated that a Kv2.1 regulatory protein modulates channel gating via effects on the association between the termini (Lvov et al, 2009).…”
Section: Discussionmentioning
confidence: 94%
“…This suggests that phosphorylation-dependent modulation of Kv2.1 requires N/C interaction. Recent studies using fluorescence resonance energy transfer demonstrated N/C interaction within Kv2.1 and suggested dynamic changes in this interaction during voltage-dependent gating (Kobrinsky et al, 2006). Analyses of the effects of altering phosphorylation state on Kv2.1 N/C interaction using such sensitive techniques may clarify the role of C-terminal phosphorylation in regulating this interaction and channel gating.…”
Section: Discussionmentioning
confidence: 99%